Investigation of the Temporal Management of Pistachio Pests Control in Iran - Mohammad Abdollahi Ezatabadi; Mahdi Basirat; Reza Sedaghat (Journal of Nuts, 2023)
In this study, we first identified the existing knowledge about temporal management of pesticide consumption. Then the growers view and performance in this regard was estimated. Comparing growers’ knowledge with experts’ idea, the pistachio producers score related to temporal management of pests control was calculated. Pistachio producers of Anar and Rafsanjan areas in Kerman province, Iran were considered as our study population. Using stratified random sampling method, a sample of 100 growers were selected. Pearson correlation, analysis of variance and regression were used to investigate the socioeconomic factors affecting growers’ knowledge and the effect of this knowledge on growers’ performance. The results showed that in the field of temporal management of pesticide use, growers’ knowledge is low. Investigating the factors affecting growers’ knowledge level showed that research, education and extension activities have had the significant effect on increasing knowledge of inputs temporal management. The results also showed that knowledge of temporal management pest control did not increase land use productivity (pistachio yield) but enhanced pesticide productivity. The amount of pesticide usage decreased by 0.477 l/ha/year, with increasing of each score to pest control knowledge. In other words, with increasing knowledge of pest control, not only the costs of spraying will be reduced, but it will also have environmental benefits. In short, current conditions are not suitable for precision agriculture application in Iranian pistachio orchards, but with increasing knowledge of growers, these conditions will be created.